Manager-Specific Effects on Earnings Guidance: An Analysis of Top Executive Turnovers - BROCHET, FRANCOIS; FAUREL, LUCILE; MCVAY, SARAH (Journal of Accounting Research, 2011)
We investigate how managers contribute to the provision of earnings guidance by examining the association between top executive turnovers and guidance. Although firm and industry characteristics are important determinants of guidance, we conclude that CEOs participate in firm-level policy decisions, whereas CFOs are involved in the formation or discussion of guidance. Among firms that historically issued frequent guidance, breaks in guidance following CEO turnovers are relatively permanent and are potentially attributable to firm-initiated changes in guidance policy. Breaks following CFO turnovers, however, likely reflect uncertainty on the part of the newly appointed executive—they are concentrated in the two quarters following the turnover, are associated with the background of the newly appointed CFO, and extend to the relative precision of the guidance. Among firms that did not issue guidance historically, we find some evidence that newly appointed externally hired CEOs increase the likelihood of providing guidance.